Public health impact of COVID-19 pandemic on the emergency healthcare system: a region-wide analysis. (20th October 2021) - Stirparo, G; Oradini-Alacreu, A; Migliori, M; Villa, GF; Botteri, M; Fagoni, N; Signorelli, C; Sechi, GM; Zoli, A
Abstract: Background: The Lombardy region has been one of the Italian regions most affected by the COVID-19 pandemic in 2020, with 22.7% of total Italian cases and 33.9% of total deaths. The emergency healthcare system was under deep stress throughout the period under consideration due to the admission of COVID-19 patients to the Emergency Department (ED) and had to be thoroughly reorganized. Methods: We performed a retrospective descriptive analysis of patients admitted into the ED recorded in the Lombardy online regional portal called EUOL. We compared the data registered in the EUOL with the patients admitted to the EDs from 1 January 2019 to 31 December 2019 and from 1 January 2020 to 31 December 2020. Results: The number of admissions to the ED decreased by 32.5% in 2020 compared to 2019, reaching the lowest number in March and April. However, the percentage of patients hospitalised after ED significantly increased in 2020 compared to 2019 (OR 1.47, p < 0.0001), reflecting the management of patients with a more severe clinical condition. Indeed, the number of patients classified as red or yellow codes at hospital admission was significantly higher in 2020 than in 2019 (p < 0.0001). Moreover, more patients arrived at the ED by ambulance in 2020 (21.7% in 2020 versus 15.1% in 2019. OR 1.56, p < 0.0001), with more than 35% of patients transported by ambulance in March and April 2020. Conclusions: Our results showed, on the one hand, inappropriate visits to the EDs by non-emergency and low complex cases in 2019 before the pandemic and, on the other hand, they also highlighted that patients in critical condition were reluctant to visit the ED due to the fear of getting infected. This analysis showed that EMS played a crucial role in the overall public health impact of the COVID-19 pandemic, increasing the percentage of patients transported to the hospital with a severe clinical condition, reorganizing and allocating resources to the areas that were most affected during the pandemic. Key messages: This is a descriptive analysis of the public health impact of the COVID-19 pandemic on the admission to Emergency Departments in 2020. Our results underline the need to monitor the pandemic's evolution in order to reorganize the hospitals that admitted the COVID-19 patients.